Developing sociolinguistic competence in the ESL classroom: a case study of ESL instructors in a Malaysian university - Abd Rahman, Siti Nadhirah; Razali, Abu Bakar; Abd Samad, Arshad; Jeyaraj, Joanna Joseph; Abdullah, Nur Surayyah (UiTM Press, 2022)
It is vital for language learners to know and express the appropriate language in different social contexts because the inability to do so could cause misunderstandings and miscommunication. The ability to perform such a task stems from an important concept in communicative competence, called sociolinguistic competence. However, being able to use the target language appropriately is especially difficult for ESL and EFL learners because they are not commonly exposed to the language and how it is being used by communicatively competent speakers. Therefore, this study reports on how ESL instructors in a Malaysian university developed students’ sociolinguistic competence in the language classroom. The methods of data collection for this study were in-depth interviews and stimulated recalls with three ESL instructors who were selected based on a list of criteria which would translate to their credibility and experience to be participants in this study. It was found that in developing their students’ sociolinguistic competence, these ESL instructors co-constructed meaning with their students, provided a positive and comfortable learning environment, as well as developed students’ sociolinguistic competence through explicit methods and classroom interaction. It is hoped that the findings of this study can guide other ESL instructors in developing their students’ sociolinguistic competence, specifically through the examples of methods and approaches that could be applied in other classrooms.